Desain Inovatif Sistem Informasi Profil Hotel Damanaka Pangalengan Berbasis Website Menggunakan UML dan Figma - j-sika; Nistrina, Khilda; Awalul Lestari, Tiara (J-SIKA|Jurnal Sistem Informasi Karya Anak Bangsa, 2024)
The hotel profile information system is a tool to convey information to tourists or customers who will be staying at the hotel. However, up until now, the hotel has not had such an information system. This has caused prospective customers planning to stay to have difficulty obtaining information about Hotel ABC. Therefore, an information system is needed that can display the hotel profile, facilities, prices, and news about the hotel. The stages in designing this profile information system use the waterfall method. The first stage is requirement analysis, carried out through observation, interviews, and literature study. This stage is conducted to gather input regarding the system to be developed and includes a literature study by collecting data from several books and other sources related to the design of the hotel information system. The next stage is design; this information system is created using StarUML and Figma. The final stage is documentation, where this stage is conducted to understand the process of conveying hotel information that has been carried out. For future research, it is hoped that the design of this hotel profile information system can be realized